Spanish Fund: subscriptions to 27th October, 1936
028-0025-001 SPANISH FUND. Subscriptions to 27th October, 1936. £.s.d General Council 1,000.0.0 Trade Unions 9,793.5.6½ Trades Councils & Labour Parties 3,249.4.9 Individual and other subscriptions 5,234.6.11½ 19,276.17.3 Remittances from America 7,117.5.6 TOTAL £26,394.2.9 292/946/28/25